Population Development and Infestation Rate of Mediterranean Fruit Fly [ Ceratitis capitata Wied. (Diptera: Tephritidae)] in Pomegranate Orchards in Sanlıurfa, Turkiye - Guler, Celal; Mamay, Mehmet; Sonmez, Ceyhan (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
Mediterranean fruit fly [ Ceratitis capitata Wied. (Diptera; Tephritidae)] is an important pest responsible for significant economic losses in several fruit species. This study determined the population development and infestation rate of Mediterranean fruit flies in pomegranate orchards situated in Akcakale, Haliliye, Karakopru, and Suruc districts of Sanl & imath;urfa province during the years 2020-2021. Three sexually attractive pheromone traps were hanged in each orchard and monitored weekly. A total of 100 fruits from randomly selected ten trees in each orchard were collected during harvest and examined to record the damage symptoms and larvae of the pest. The first flight of the pest was recorded in August and a lower population was noted during 2020 compared to 2021. The population was low in the summer, while it was high in the autumn months, particularly in Akcakale and Suruc districts. The highest population (17 adults/traps) during 2020 was recorded on October 16th in the Suru & ccedil; orchard while it reached 565 adults/traps on November 19th in Akcakale and 216 adults/traps on September 25th in the Suru & ccedil; district. Although varied across years and locations, two population peaks were recorded with an active period of 1-5 months between August and December. The total number of adults caught in the traps during the active period was 21 and 312 adults/trap in Karakopru, 125 and 1353 adults/trap in Suruc, 26 and 1226 adults/trap in Akcakale, and 29 and 259 adults/trap in Haliliye during 2020 and 2021, respectively. The infestation rate was 0% and 1% in Suruc and 1% and 4% in Ak & ccedil;akale during 2020 and 2021, respectively. The pest did not exert any damage to the pomegranate orchard in the Haliliye and Karak & ouml;pr & uuml; districts during both years. The adult flight of the pest was recorded at the end of summer and population increase during autumn indicated that the pest could not overwinter in & Scedil;anl & imath;urfa. Hence, the pest did not exert any economic damage to the pomegranate orchards of & Scedil;anl & imath;urfa, however, higher population density during 2021 suggests that it could become an economic pest in the future. For this reason, pomegranate producers must be informed about the pest through training and extension activities. Pomegranate producers should be advised to harvest pomegranate without delay and collect and destroy infested fruits on the trees and fallen on the ground.
Keywords: Ceratitis capitata; Population; Infestation; Pheromone; Pomegranate